Romania : Strengthening Inclusion and Improving Effectiveness for Social Assistance Benefits - World Bank (Washington, DC, 2014)
Despite the overall successful picture of sustained economic growth, a significant share of Romanians live in absolute poverty and deep pockets of poverty still remain, pointing to the need of more inclusive and effective social safety nets. During recent years Romania made efforts to redistribute the benefits of growth by keeping constant the share of GDP devoted to social protection; still, the per capita expenditure on the main social assistance benefits is amongst the lowest in EU. Compared with the EU average, Romania has a good mix of targeted/ non-targeted social assistance programs, but they provide only a modest protection of the poor against income vulnerability, and at a relatively high cost. Taken together, the safety net benefits cover 71 percent of the poor. Some key issues and challenges for Romania are: The 'leakages' of social assistance cash transfers has increased, while performance in covering the poverty gap weakened. Spending on poverty targeted programs has decreased relative to GDP and so has the capability of these benefits to adequately cover the basic needs of the poor. The high number of programs and the heterogeneity of the eligibility thresholds/criteria for different benefits translate into a rather fragmented and difficult to monitor system of social assistance benefits. The report describes several policy options or recommendations, among them: Strengthen social inclusion by increasing access of the poor to social assistance benefits. Improve effectiveness by further consolidation of the system and improved monitoring. Strengthen the linkages between social assistance, education, and labor policies.